An exploration of the impact of development intervention programmes on poverty: a case study - Matemba, Lawrence (Graduate School of Business (GSB), 2024)
[page 139,140,166 are missing] Challenges that development intervention programmes face do not only pertain to poor programme design, implementation, management and evaluation, but more importantly the underlying mindset assumptions that inform them lack the necessary alignment with the local contextual mindset and worldview in which programmes themselves are undertaken. Put differently, development is not a purely economic, technological or political problem. Its success is frequently dependent on an understanding of the society in which it is to take place, knowledge of the social and cultural factors that condition the community's responsiveness to developmental change, and the ability to obtain willing cooperation of the beneficiaries involved (Amon, 1991). While existing development intervention programme designs and evaluation approaches have proved extremely powerful in explicating: (a) how programmes work (Asian Development Bank, 1998), (b) what impact they have (Barker, 2000), and (c) why they work as they do (Kruse, Kyllonen, Ojanpera, Riddell, and Vielajus, 1997), they are beginning to reveal the limits of their applicability, especially in rural and semi-rural settings. Less effort has been focused on the worldview and mindset assumptions that underlie the design and implementation of these programmes, especially their alignment with those of the community in which they are implemented. The aim of this dissertation was to explore and develop insights relating to development intervention programmes from a traditional and Western mindset, when directly transposed in a developing world context - thereby highlighting the gaps and inefficiencies of a non-contextualised approach. In particular, the underlying traditional mindset assumptions under consideration are analysed in their developmental and historical setting, problems are pointed out and opportunities are identified. In addition, high level goals are then identified and refined to address such problems and meet the opportunities. Requirements are then elaborated upon to meet these goals. While conducting this research, oral sources were an invaluable source of information. Conducting the interviews was both intellectually stimulating and academically challenging. The practical aspect of the interviews was fascinating and the relationship I developed with my interviewees during this period, most of whom I had known while doing pastoral work at St. Vincent's Catholic Parish between 1992 and 1993, and in 1996 will be cherished forever.